Tests for Suspected Inborn Errors of Metabolism - J Gordon Millichap (Pediatric Neurology Briefs)
The initial laboratory assessment of infants and children with suspected inborn errors of metabolism (IEM) is reviewed by the Department of Medical Genetics, Mayo Clinic, Rochester, MN.